THE RELATIONSHIP OF FAMILY SUPPORT REGARDING THE PATIENTS WITH CHRONIC KIDNEY FAILURE WHO HAVE HEMODIALIZED THERAPY TREATMENT IN PMI HOSPITAL BOGOR: HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN PASIEN GAGAL GINJAL KRONIS YANG MENJALANI TERAPI HEMODIALISA DI RS PMI KOTA BOGOR - Sara Sara Tania Aprianty; Hani Siti Hanifatun Fajria (Jurnal Ilmiah Wijaya, 2018)
Chronic Renal Failure (CRF) is a disease that has occurred after various diseases that damage the kidney nephrons period up to the point the two are not capable of functioning regulatory and ekstetoriknya to maintain homeostasis. Number of patients with kidney failure in Indonesia is estimated to reach 300.000 people. As many as 12.804 patients with renal failure undergoing hemodialysis. To determine correlation family support patient compliance with chronic renal failure undergo hemodialysis therapy in RS PMI Bogor. This type of research is descriptive quantitative analytical research with cross sectional design. How sampling in this study with purposive sampling with a sample of 152 respondents. The instrument used is questionnaire while data analysis techniques using univariate and bivariate analysis using statistical test Chi-Square. Of the 152 respondents with a family to support as many as 139 respondents (91.4%), adherent patients as many as 128 respondents (84.2%) and family support with adherent patients as many as 121 respondents (79.6%). Statistical test results using Chi-square test p value value 0,007 (p <0.05) and the value of OR 5.762. The conclusion of this research that, There is a correlation between family support patient compliance with chronic renal failure through hemodialysis therapy in PMI Hospital Bogor, 2016. The researchers recommend that increased family support by distributing leaflets to the patients and families about the importance of family support for compliance patients undergo hemodialysis therapy.